Studies on Cellulose Acetatephthalate II, Polarographic Studies of Ion Binding-Cadmium Cellulose Acetate Phthalate - P. Patel, Chandrakant; H. Garg, Dinesh; C. Trivendi, Harikrishna (Asian Journal of Chemistry, 2010)
The polarographic method of analysis was applied to study cadmium ion binding in cellulose acetate phthalate (CAP) solutions. It has been observed that the degree of free ions virtually remains constant in wide range of concentrations of CAP solutions and decreases with degree of neutralization. The results are interpreted according to Oosawa's two phase model of polyelectrolytes.